HUBUNGAN PERUBAHAN PSIKOLOGI TERHADAPPREMENSTRUAL SYNDROME PADA REMAJA PUTRI - Liandani, Meri (Akbid Wirabuana, 2023)
Premenstrual Syndrome (PMS) is a symptom felt by women 3-7 days before menstruation. If not noticed,it will have an impact on women's productivity and health. PMS causes symptoms not only physicallybut also psychologically. The WHO (World Health Organization) report explains that PMS symptomsare experienced in 65.7 of young women. Symptoms of PMS can be increased when the hormonalchanges in a woman happen, which changes level of estrogen hormone will affect the levels of serotoninin the body. It affect the psychological factors in women and some manifestation will be appear such asbehavioral changes, physical, and mood. The purpose of this study was to determine the relationshipbetween psychological changes to premenstrual syndrome in adolescent girls of SMK GaneshaSekampung. This type of research uses quantitative methods with a cross sectional approach. In thisstudy the number of samples was 60 samples using total sampling techniques. And Data collection usingquestionnaires.